Alterations of brain activity in fibromyalgia patients - Passakorn Sawaddiruk (2018)
© 2017 Elsevier Ltd Fibromyalgia is a chronic pain syndrome, characterized by widespread musculoskeletal pain with diffuse tenderness at multiple tender points. Despite intense investigations, the pathophysiology of fibromyalgia remains elusive. Evidence shows that it could be due to changes in either the peripheral or central nervous system (CNS). For the CNS changes, alterations in the high brain area of fibromyalgia patients have been investigated but the definite mechanisms are still unclear. Magnetic Resonance Imaging (MRI) and Functional Magnetic Resonance (fMRI) have been used to gather evidence regarding the changes of brain morphologies and activities in fibromyalgia patients. Nevertheless, due to few studies, limited knowledge for alterations in brain activities in fibromyalgia is currently available. In this review, the changes in brain activity in various brain areas obtained from reports in fibromyalgia patients are comprehensively summarized. Changes of the grey matter in multiple regions such as the superior temporal gyrus, posterior thalamus, amygdala, basal ganglia, cerebellum, cingulate cortex, SII, caudate and putamen from the MRI as well as the increase of brain activities in the cerebellum, prefrontal cortex, anterior cingulate cortex, thalamus, somatosensory cortex, insula in fMRI studies are presented and discussed. Moreover, evidence from pharmacological interventions offering benefits for fibromyalgia patients by reducing brain activity is presented. Because of limited knowledge regarding the roles of brain activity alterations in fibromyalgia, this summarized review will encourage more future studies to elucidate the underlying mechanisms involved in the brains of these patients.